New Development of Reverse Micelles and Applications in Protein Separation and Refolding - 刘杨 董晓燕 孙彦 (Chinese journal of chemical engineering, 2008)
Reverse micelles bring mild and effective microenvironments in organic solvent that contain bitmolecules, which have attracted immense attention for application in the isolation of proteins, protein refolding, and enzymatic reaction. In this review, the application of reverse micelles for protein separation and refolding has been briefly summarized and various reverse micellar systems composed of different surfactants, including ionic, non- ionic, mixed, and affinity-based reverse micelles, have been highlighted. It illustrates especially the potential application of the novel affinity-based reverse micelles consisting of biocompatible surfactant coupled with affinity ligands. Moreover, the importance to develop universal affinity-based reverse micelles for protein separation and refolding in the downstream processing of biotechnology has been pointed out.